Stability of cyflumetofen resistance in Tetranychus cinnabarinus and its correlation with glutathione‐S‐transferase gene expression. Issue 10 (25th March 2019) - Feng, Kaiyang; Yang, Yuwei; Wen, Xiang; Ou, Shiyuan; Zhang, Ping; Yu, Qian; Zhang, Yichao; Shen, Guangmao; Xu, Zhifeng; Li, Jinhang; He, Lin
Abstract: BACKGROUND: Cyflumetofen is an outstanding acaricide with a novel mode of action. Tetranychus cinnabarinus, an important agricultural pest, is notorious for developing resistance to most classes of acaricides rapidly and results in enormous loss for the economy. Our previous study had pointed out glutathione S‐transferase (GSTs) significantly contributed to the cyflumetofen‐resistance formation in T. cinnabarinus, but the more specific mechanism needed to be further investigated. RESULTS: The unstable resistance was observed in cyflumetofen‐resistant strain (CyR)under acaricide‐free condition. The activity of GSTs increased along with the development of resistance. The expressions of 13 GST genes were detected in CyR and susceptible strain (SS), of which six genes were overexpressed in CyR and the TcGSTm02 was selected as the representative for functional study. The expression of TcGSTm02 changed along with the resistant level of CyR with the same trend. Recombinant protein of TcGSTm02 with high activity was successfully obtained by E. coli expression system, whose activity could be inhibited by cyflumetofen (IC50 = 0.23 mM). Recombinant TcGSTm02 could effectively decompose cyflumetofen, and catalyze GS − to conjugate with cyflumetofen. CONCLUSION: All clues confirmed that GSTs strongly associated with cyflumetofen‐resistance and a representative gene, TcGSTm02, showed function on contributing the evolution of cyflumetofen‐resistance in T. cinnabarinus . © 2019 Society of Chemical Industry Abstract : A strong correlation between glutathione S‐transferase and cyflumetofen‐resistance in Tetranychus cinnabarinus .